Proposal of Flowable Fill Designs for improvement of excavation and filling works of trenches in sanitation systems - Cruz, J. (2020)
Population grow in recent years requires an extension of the current pipeline sanitary system. For this purpose, granular excavation and landfill works are associated with pedestrian traffic congestion. Therefore, it is necessary to develop an innovative and sustainable alternative to reduce the problems generated during the execution of the conventional process. This research proposes the use of flowable fill due to the multiple advantages offered by this material. On the one hand, it is economical for medium to large trench fill volumes, considering savings in labor (it is done with a small number of workers), in equipment (does not require the rental or purchase of compaction equipment) and in time (the pouring is done by directly pumping the mixture, from the mixing machines to the excavation). On the other hand, being self-compacting and self-leveling decreases the width of the trenches, reducing excavation and filling volumes; which, in turn, incur money savings. Also, this material guarantees work safety, since people are not required inside the excavation and fill in poorly accessible areas without any problem. Dosages were established for ten flowable fill mixtures with cement contents of 50, 60, 70, 80 and 90 kg of cement and a range of admixture from 1.75 to 2.00%; The results indicated that decreasing the fine aggregate - coarse aggregate ratio, the compressive strength of the mixtures increases and the slumps of the mixtures decreases, and the compressive strength increases directly proportional to the cement content.